Architects' and interior designers' perception of the needs of users in residential spaces (Estudos em Design, 2015)
The article aims to find out how architects and interior designers identify the spatial needs of their customers and how these requirements are translated into projects. In order to do this, the city of Caruaru-PE was taken as the spatial area and exploratory field research through structured interviews was carried out amongst this segment of professionals. The data which was collected analysed and qualitatively discussed show that systematic research into customers ́ needs has been missing in the work of these professionals and that the functional needs of the future users of their projects are considered more important than aesthetic considerations.
Keywords: interior design; residential spaces; spatial needs